Effect of Coriolis acceleration on the span-wise vorticity field over a wind-turbine airfoil - Rodrigues, Pedro T. [UNESP]; Gennaro, Elmer Mateus; Souza, Daniel S. [UNESP]; AIAA (Amer Inst Aeronautics & Astronautics, 2022)
The rotation is known to reduce the volume of the region of separated flow on inboard sections of horizontal-axis wind turbine blades. This reduction is frequently attributed to centrifugal pumping. However, recent investigations on the rotational stabilization of leading-edge vortex suggest that the radial transport of vorticity may not be the dominant mechanism limiting the vortex circulation on inboard sections of insect wings. For such low-Reynolds number, the effect of the tangential component of the Coriolis force destroys radial vorticity, limiting the growth of the leading-edge vortex and stabilizing it. However, to the best knowledge of the authors, the contribution of such a phenomenon to the rotational augmentation observed in wind turbines has not been assessed. We employed quasi-3D simulations to investigate the role of the Coriolis acceleration to the balance of span-wise vorticity within the region of separated flow on the upper surface of wind-turbine-blade sections at high angles of attack. The destruction rate of radial vorticity due to Coriolis acceleration was most significant in the free shear layer on the upper boundary of the separated-flow region. Moreover, it is shown that its integrated effect may be comparable to the rate of vorticity flowing in the recirculation region from the boundary layer. Therefore, the mechanism may be relevant to rotational augmentation observed in inboard sections of wind-turbines blades.